Pola Komunikasi Guru Pendidikan Agama Islam dan Siswa di SMP Negeri 1 Pleret Bantul Yogyakarta - Purbasari, Wulan; Nurmawati, Liana (Attractive : Innovative Education Journal, 2022)
The research entitled Communication Patterns of Islamic Religious Education Teachers and Students at SMP N 1 Pleret Bantul Yogyakarta was motivated by the researcher's curiosity about communication patterns between teachers and students in classroom learning. In the implementation of learning in the classroom, the teacher applies direct communication to students by providing learning material, namely (Knowing Allah through His Name) but the material is not conveyed properly to students if the communication pattern made by the teacher to students is less effective. Therefore, the purpose of this study was to determine the pattern of communication between teachers and students in learning (Knowing Allah through His Name) in the classroom. This research is a type of qualitative-descriptive research, the researcher conducts interviews with key-informants and informants. This research refers to Lasswell's theory. To measure communication patterns, researchers used descriptive qualitative methods by conducting direct observations and interviews. Through research that has been carried out by researchers, communication between teachers and students in learning material religious education (Knowing Allah through His Name) is effective. Both teachers and students can understand each other's material, fun in learning activities can have a good influence, and students develop and learn according to teacher expectations and directions Keywords: Teacher Communication Pattern, Teacher Communication, Students Communication Pattern